1995
DOI: 10.1002/ar.1092410106
|View full text |Cite
|
Sign up to set email alerts
|

Variation in articular cartilage in rabbits between weeks six and eight

Abstract: Our results indicate that the synthesis of matrix components becomes more important relative to proliferative activity. The traditionally defined histological layers (zones I, II, III, and IV) are not clearly distinguishable in rabbits of this age. In 6- and 7-week old animals only a "surface" (I/II) and a "deep" layer (III) can be distinguished. By 8 weeks, zones I and II are well defined but the mineralization front (marking the boundary between zones III and IV) is still absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…There are two contrasting reasons for the stark decline in cell density. It has been reported by several authors (Stockwell 1971;Eggli et al 1988;Oreja et al 1995), that the density of the surface zone decreases during growth and whilst not measured specifically here, comparison of representative micrographs (Fig. 2) suggest the same is true for Monodelphis.…”
Section: Stereologymentioning
confidence: 54%
See 1 more Smart Citation
“…There are two contrasting reasons for the stark decline in cell density. It has been reported by several authors (Stockwell 1971;Eggli et al 1988;Oreja et al 1995), that the density of the surface zone decreases during growth and whilst not measured specifically here, comparison of representative micrographs (Fig. 2) suggest the same is true for Monodelphis.…”
Section: Stereologymentioning
confidence: 54%
“…Two proliferative bands were evident; one above the subchondral plate, the other just beneath the articular surface. Similarly, Oreja et al (1995) reported intense proliferative activity in surface zone chondrocytes in rabbits at 6 weeks of age. At skeletal maturity, cell proliferation halts and no chondrocyte cell proliferation is observed (Mankin 1962a(Mankin , b, 1963Rigal 1962).…”
Section: Introductionmentioning
confidence: 94%
“…Thus, in the mature state, the cartilage organization is characterized by a high degree of anisotropy. (18,19) All layers were not clearly differentiated in the histologic images and most of the cartilages included in this study appeared to consist of two regions: region I including the superficial and the transitional layers and region II corresponding to the deep layer and calcified cartilage.…”
Section: Control Cartilagesmentioning
confidence: 79%
“…1 ). As the thickness, cell density, physical characteristics, and biochemical characteristics of articular cartilage have been shown to vary according to mechanical load, 26 , 27 explants were harvested from weight-bearing surfaces only in order to permit standardization.…”
Section: Methodsmentioning
confidence: 99%